Design and Operation of a Concentric-Fiber Displacement Sensor - Yasin, Moh; Harun, Sulaiman Wadi; Kusminarto, -; Karyono, -; Zaidan, Andi H.; Thambiratnam, Kavintheran; Ahmad, Harith (Taylor & Francis, 2009)
A concentric-fiber displacement sensor is demonstrated using a developed theory to support the experimental findings. The theoretical analysis uses an electromagnetic Gaussian beam approach to determine the transfer function of the sensor. The sensor has two operating ranges with a good linearity; namely, the front slope and back slope. On the front slope, the sensitivities are obtained at 3.6 and 2.1 mW/m for the theoretical and experimental approaches, respectively; while on the back slope the sensitivities are 1.6 and 0.52 mW/m for theoretical and experimental approaches, respectively. This sensor has many potential applications such as automated monitoring control, position control, and micro-displacement sensing in the hazardous regions.